Caribbean Report 17-01-1995 - Ransome, Debbie (anchor); Fletcher, Pascal (correspondent); Carrington, Edwin (interviewee); Hayes, Rosie (correspondent); Fraser, Tony (correspondent); Worme, Philip (correspondent); Crosskill, Hugh (correspondent); Baldry, Tony (interviewee) (The British Broadcasting Corporation, 1995)
In this report, Cuba pushes for a CARICOM Trade Office to be established in Havana. CARICOM Secretary-General Edwin Carrington indicated that CARICOM was reluctant to take up the offer at this time. Rosie Hayes questioned Mr. Carrington on whether the US embargo on Cuba contributed towards this decision. In Trinidad and Tobago, Tony Fraser reports on the ruling of High Court Judge Margot Warner to allow a 12 year old Muslim girl to wear her religious head covering (hijab) to a Catholic school. Holy Name Convent debarred Sumayyah Mohammed from attending classes while wearing a hijab. Journalist Philip Worme reports on whether Haitians and US peacekeepers would be able to police the country following the withdrawal of US troops. Hugh Crosskill reports that British Labor Party MP Bernie Grant has written to the Ministry of Defense to denounce plans to exclude Caribbean Head of States from the VE Day celebrations in May. Tony Baldry speaks on the potential of Puerto Rico to British business interests as they seek to broaden their investments in the Spanish-speaking Caribbean.
1. Headlines with Debbie Ransome, anchor (00:00-00:33)
2. Report on Cuba's push for a CARICOM Trade Office in Havana (00:34-00:52)
3. Pascal Fletcher reports on Cuba's increasing relations with CARICOM (00:53-02:12)
4. Interview with Edwin Carrington on CARICOM's reluctance to take up the offer and whether the US embargo contributed towards this decision (02:13-04:24)
Keywords: Cuba -- Foreign relations -- Caribbean Area; Cooperation -- Caribbean Area; Judgements -- Trinidad and Tobago; School attendance -- Trinidad and Tobago -- Religious aspects; Haiti -- Politics and government; Democracy -- Haiti; Haiti -- Foreign relations -- United States; Social change -- Haiti; Great Britain -- Foreign relations -- Caribbean Area; V-E Day, 1945 -- Great Britain; Great Britain -- Foreign economic relations -- Puerto Rico; Great Britain -- Commerce; Hijab (Islamic clothing) -- Trinidad and Tobago